2020
DOI: 10.3390/plants9121744
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile, Safety Assessment and Wound Healing Activity of Artemisia absinthium L.

Abstract: The aim of study was to validate, by in vitro and in vivo studies, the traditional use for wound-healing activity of Artemisia absinthium L. Reversed-phase liquid chromatography coupled with diode array detection and electrospray ion trap mass spectrometry (RP-LC-DAD-ESI-MS) analysis allowed to identify eleven polyphenols with chlorogenic acid as the most abundant compound (3.75 g/100 g of dry extract). After that, antibacterial activity as well as acute dermal and oral toxicity were assessed in animal models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
15
2
Order By: Relevance
“…A recent study [44] of A. absinthium methanol extract has indicated MIC 2.5-1.255 mg/mL towards Escherichia coli ATCC 10536, while in our study it exhibited MIC 4 mg/mL towards E. coli (IBRS E003) resistant strain. Unlike high susceptibility of resistant P. aeruginosa strain recorded in our study, in the study by Boudjelal et al [44], it did not show activity (MIC > 2.5 mg/mL) as well as the one by Khan et al [45]. Methanolic extract studied previously by Hasannezhad et al [46] has shown MIC 41.7 mg/mL towards L. monocytogenes PTCC 1298, unlike 4 mg/mL determined in our study.…”
Section: Antimicrobial Capacity Of a Absinthium L And Insights Into The Modes Of Actioncontrasting
confidence: 53%
“…A recent study [44] of A. absinthium methanol extract has indicated MIC 2.5-1.255 mg/mL towards Escherichia coli ATCC 10536, while in our study it exhibited MIC 4 mg/mL towards E. coli (IBRS E003) resistant strain. Unlike high susceptibility of resistant P. aeruginosa strain recorded in our study, in the study by Boudjelal et al [44], it did not show activity (MIC > 2.5 mg/mL) as well as the one by Khan et al [45]. Methanolic extract studied previously by Hasannezhad et al [46] has shown MIC 41.7 mg/mL towards L. monocytogenes PTCC 1298, unlike 4 mg/mL determined in our study.…”
Section: Antimicrobial Capacity Of a Absinthium L And Insights Into The Modes Of Actioncontrasting
confidence: 53%
“…The values of the phenolic compound contents found in our extracts are lower than those obtained by Boudjelal et al [ 43 ] (180.33 ± 16.25 mg GAE/g DE). On the other hand, the values obtained from the present study are higher than those found by Kružinauskaitė et al [ 44 ], whose phenolic compound content of A. absinthium extracts varies from 21.19–24.74 mg GAE/g ED.…”
Section: Resultscontrasting
confidence: 90%
“…A methanolic extract of Artemisia annua was used for the first time for the composition of a wound dressing that was shown to increase proliferation of L929 fibroblast cells but only after 4 days of incubation and to exert potent antibacterial activity [ 43 ]. Furthermore, accelerated wound healing was described in other Artemisia species [ 44 , 45 ]. Rhimi et al (2019) has reported enhanced wound healing in mice by using an ointment of the ethanolic extract of Dittrichia viscosa , family Asteraceae [ 46 ].…”
Section: Resultsmentioning
confidence: 99%